Answer:
Yes
Step-by-step explanation:
6((3×5)-5)
6(15-5)
6(10)
60
Hope this helps!! :)
Always get rid of denominators first. Multiply both right and left side by 6
-7 (6) = -c (6)/6 + 12(6)
-42 = -c + 72
c = 72 +42
c = 114
rearrange like terms together
42 = 18 - 4x
4x = 18 -42
4x = -24
divide both sides by 4
x = -6
Answer:
Step-by-step explanation:
F=I(1+r)^t
500=225(1.15^t)
t=ln(500/225)/(ln1.15)
t=5.713 years
Answer: a) 1024, b) 1, c) 64 and d) 0.125.
Step-by-step explanation:
Since we have given that
(a)
As we know that
So, it becomes,
(b)
As we know that
c)
As we know that
(d)
As we know that
Hence, a) 1024, b) 1, c) 64 and d) 0.125.
Make Martina as x, then austin is x+8, brian is 2(X+8). X+(X+8)+2(X+8)=92,
4x=92-8-16,
X=17
M is 17, A is 25, B is 50